Implementasi Program Bimbingan Belajar Dalam Mengatasi Kesulitan Belajar Siswa Kelas IX (Studi Kasus Di Smp Muhammadiyah Al-Kautsar Program Khusus Kartasura Tahun Pelajaran 2015/2016) - Nuraini, Latifah; , Drs. Arief Wibowo, M.Ag (2016)
Muhammadiyah Al-Kautsar Secondary School of Kartasura for Special Programme has the learning guidance programme called academic coaching. This programme is made for giving facility for the students who have difficulties in studying. This programme uses consultative direction approach, giving material and strategy for the students at ninth grade, because they will have final examination. They need this programme for giving facility in their studying in final examination subject. So the statement of the problem is how the implementation of learning guidance programme is to overcome the learning difficulties of the students, and what the supporting and obstacling factors are in the implementation of learning guidance programme to overcome the difficulties of the study of grade of ninth at Muhammadiyah Al-Kautsar Secondary School of Kartasura for Special Programme in the academic year 2015/2016. The purposes of this research are to describe the implementation of the programme of learning coaching in solving the students' difficulty in learning and to describe the supporting and the obstacle factors in the implementation of the programme of learning coaching in solving the difficulty in learning of the Grade IX students in Muhammadiyah Al-Kautsar Secondary School of Kartasura for Special Programme in the academic year of 2015/2016. This research uses a field research applying a qualitative research approach. The methods which used are interview, observation, and documentation. Meanwhile, the analysis method has used a descriptive-qualitative with applying an inductive analysis. Based on the data analysis conducted, it can be concluded that the implementation of the programme of learning coaching in Muhammadiyah Al-Kautsar Secondary School of Kartasura for Special Programme is by forming six small groups consist of 5-6 students. This grouping is based on the ability of the student's learning. This learning ability is viewed from the subjective assessment from the teachers and the results of try out. The method of teachers' teaching in giving the coaching is based on the students' learning style that is like their own friend. It is conducted in order that the students are more relaxed and not being ashamed to ask questions. The evaluation step and follow-up from this programme is the outcomes reached during this learning coaching that is the emergence of gradual increase in all subjects of every student of Grade IX. This evaluation is conducted by every teacher by giving remedial and richness. The supporting factors from this programme are: the teachers in Muhammadiyah Al-Kautsar Secondary School of Kartasura for Special Programme are mostly young with an above-average ability level , supports from the student's guardians and from the school sides (headmaster and Daily Executive Board), and the sufficient infrastructure. Meanwhile, the obstacle factors are: the limited time of the implementation and the students were not academically selected in the stage of enrolling to this junior high school.